The world food situation: recent developments, emerging issues, and long-term prospects - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul; Rosegrant, Mark W. (International Food Policy Research Institute, 1997)
This report comes out of ongoing IFPRI research and activities conducted as part of the 2020 Vision for Food, Agriculture, and the Environment initiative, which aims to generate information to eradicate hunger, prevent poverty, and protect the environment.